Pengaruh profitabilitas, capital intensity, dan leverage terhadap agresifitas pajak pada perusahaan perbankan yang terdaftar di BEI tahun 2016-2020 - Dewi, Ari Ani Kusuma; Oktaviani, Rachmawati Meita (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to test whether profitability, capital intensity and liquidity have an effect on tax aggressiveness. This research is included in quantitative research, using secondary data in the form of annual reports or company financial statements. The objects in this study are banking companies listed on the Indonesia Stock Exchange for the 2016-2020 period, with the number of samples used as many as 26 companies. Sampling was carried out using a non-probability sampling purposive sampling method, with the criteria of 1) banking companies that were consistently listed on the IDX for the 2016-2020 period, 2) banking companies that presented financial statements in rupiah currency for the 2016-2020 period, 3) companies banking company banking that has a financial year ending on December 31 for the 2016-2020 period, 4) banking companies that are not at the break-even point or experiencing losses during the 2016-2020 period, 5) corporate banking that does not have an ETR value <0 or > 1. This study uses panel data regression analysis technique using Eviews 12. The results of this study indicate that the profitability variable has a significant negative effect on tax aggressiveness, the capital intensity variable has no significant effect on tax aggressiveness, and the leverage variable is not significant. effect on tax aggressiveness.